Pengaruh Model Pembelajaran Group Investigation Terhadap Hasil Belajar Siswa Pada Materi Ikatan Kimia di SMA Negeri 1 Tondano - Kristiyani Teke; Anderson Aloanis (Oxygenius Journal Of Chemistry Education, 2022)
This study aims to determine whether there is an effect of the Group Investigation learning model on student learning outcomes in understanding chemical bonding material. The research method used is the experimental method. The sample in this study were students of class X IPA 2 as the experimental class and students of class X IPA 4 as the control class. Each sample consists of 24 respondents, and the total number of respondents is 48. The data collection technique is the post-test. The post-test data analysis of the two groups used the t test. The results showed that the value of tcount was 4,399> ttable 1,717, so it could be concluded that there was a variable effect (X / group investigation) on the variable (Y / learning outcomes) so Ha was accepted and H0 was rejected. So it can be concluded that there is an effect of the Group Investigation learning model on student learning outcomes on chemical bonding material at SMA Negeri 1 Tondano.